Effect of Pornography Exposure on Junior High School Teenagers of Pontianak in 2008 - Supriati, Euis; Fikawati, Sandra (UI Scholars Hub, 2009)
Adolescent is a vulnerable group in reproductive health area. This period is marked by strong desire to try and explore new things. Pornography is a medium which can influence adolescent toward high risk sexual behaviour. The exposure to pornographic materials is a serious problem among adolescent since it could have negative impacts such as unwanted pregnancy, unsafe abortion, sexually transmitted diseases and HIV-AIDS. This cross-sectional study was conducted to understand various types of pornographic exposures, effects of pornographic exposure, and factors influence the effect. Study was conducted at five state junior high schools in Pontianak District in 2008 with 395 respondents from December 2007 to January 2008. The result shows that 83.3 % adolescence has exposed to pornography and 79.5% of them had experienced the effects of pornographic exposure. 19.8% respondent who experienced the effects of pornography was in the addiction stage. 69.2% respondent of those in addiction stage was in escalation stage. 61.1% respondent of escalation stage was in desensitization stage, and 31.8% respondent of desensitization was in act-out stage. Multivariate analysis shows that there were four variables that have significant relationship to the effect of pornographic exposure, that is gender (male), grade at school (third), length of exposure (recent) and frequency of exposure (often). The analysis also shown that the frequency of pornography (often) is the most dominant factor related to the effect of pornographic exposure among adolescence with Odds Ratio of 5.02 (95% CI: 1.39-18.09). It is suggested to provide information in a professional way and targeted to the right group; to improve preventive efforts through collaboration within school, and to study further as to align positively those in the act-out stage.